2020
DOI: 10.1021/acs.est.9b07162
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Neonicotinoids in Chinese Apiculture and a Corresponding Risk Exposure Assessment

Abstract: Neonicotinoids are the most widely used insecticides worldwide, but there is mounting evidence demonstrating that they have adverse effects on nontarget organisms. However, little is known about the extent of environmental neonicotinoids contamination in China. In this study, a total of 693 honey samples from across China, from both Apis melifera and Apis cerana, were analyzed to examine neonicotinoid concentrations and their geographical distribution, and correlation with the primary plant species from which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…The Environmental Protection Agency estimated neonicotinoid contamination of 0.04–269 μg/kg for surface water and 58.0–320.0 μg/kg for groundwater. Notably, Lu and co-authors reported approximately 65–79% of fruits and vegetables from the U.S Congressional Cafeteria and Hangzhou of China contained more than one neonicotinoid, and over 38% contained more than three neonicotinoids . In addition, a recent study reported that approximately 40% of honey samples contained at least one neonicotinoid with a residual level of 1.0–50.0 μg/kg, which were most frequently used in mainland China (IMI, ACE, THI, THM, CLO). , Different areas and various types of crops generate multiple co-exposure to pesticides with distinct concentrations and patterns in the environment …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Environmental Protection Agency estimated neonicotinoid contamination of 0.04–269 μg/kg for surface water and 58.0–320.0 μg/kg for groundwater. Notably, Lu and co-authors reported approximately 65–79% of fruits and vegetables from the U.S Congressional Cafeteria and Hangzhou of China contained more than one neonicotinoid, and over 38% contained more than three neonicotinoids . In addition, a recent study reported that approximately 40% of honey samples contained at least one neonicotinoid with a residual level of 1.0–50.0 μg/kg, which were most frequently used in mainland China (IMI, ACE, THI, THM, CLO). , Different areas and various types of crops generate multiple co-exposure to pesticides with distinct concentrations and patterns in the environment …”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, a recent study reported that approximately 40% of honey samples contained at least one neonicotinoid with a residual level of 1.0− 50.0 μg/kg, which were most frequently used in mainland China (IMI, ACE, THI, THM, CLO). 14,15 Different areas and various types of crops generate multiple co-exposure to pesticides with distinct concentrations and patterns in the environment. 16 Bioaccumulation and its corresponding risk to mammals of neonicotinoids have attracted more and more attention in recent decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of systemic insecticides, especially neonicotinoids, is well documented as causing global pollinator decline (Goulson, 2013). Acetamiprid (ACE) and imidacloprid (IMI), are the two most frequently detected neonicotinoids in agricultural products and honey in China (Wang et al, 2020). Both are currently legal in China, despite being highly toxic to a broad range of insects and other animals, especially to birds and earthworms (Pisa et al, 2015).…”
Section: Neonicotinoid Insecticides In Efn Is a Potential Threat To N...mentioning
confidence: 99%
“…Pesticide applications are regarded as the main factor for the morbidity and mortality of the colonies. [8][9][10][11] Honeybees can be exposed to pesticide residues through direct spraying and through contact with treated food (such as pollen, beebread and honey). The bee toxicity of many pesticides has been screened in North America, 12 Europe, [13][14][15] China 16 and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Some potential hypotheses, including chemical contamination, 5 global climate change 6 and bee pathogens, 7 have been proposed. Pesticide applications are regarded as the main factor for the morbidity and mortality of the colonies 8–11 . Honeybees can be exposed to pesticide residues through direct spraying and through contact with treated food (such as pollen, beebread and honey).…”
Section: Introductionmentioning
confidence: 99%